2015
DOI: 10.1208/s12248-015-9826-5
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Morphine and Its Metabolites in Infants and Young Children After Congenital Heart Surgery

Abstract: ABSTRACT. The objective of this study was to characterize morphine glucuronidation in infants and children following cardiac surgery for possible treatment individualization in this population. Twenty children aged 3 days to 6 years, admitted to the cardiovascular intensive care unit after congenital heart surgery, received an intravenous (IV) loading dose of morphine (0.15 mg/kg) followed by subsequent intermittent IV bolus doses based on a validated pain scale. Plasma samples were collected over 6 h after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…This is the first study to describe the population pharmacokinetics of morphine and its glucuronide metabolites in neonates with HIE receiving hypothermia. Similar to previous morphine population pharmacokinetic models in neonates without HIE and young children, morphine pharmacokinetics were adequately described by a 2‐compartment model for morphine and 1‐compartment model for each of the metabolites . The major study finding was that morphine clearance was markedly lower in neonates with HIE receiving hypothermia compared with reports in full‐term normothermic neonates <7 days old without HIE .…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…This is the first study to describe the population pharmacokinetics of morphine and its glucuronide metabolites in neonates with HIE receiving hypothermia. Similar to previous morphine population pharmacokinetic models in neonates without HIE and young children, morphine pharmacokinetics were adequately described by a 2‐compartment model for morphine and 1‐compartment model for each of the metabolites . The major study finding was that morphine clearance was markedly lower in neonates with HIE receiving hypothermia compared with reports in full‐term normothermic neonates <7 days old without HIE .…”
Section: Discussionsupporting
confidence: 54%
“…For example, the pharmacokinetics of morphine in neonates is already known to be highly variable, and therefore, variation in morphine pharmacokinetics in neonates with HIE receiving hypothermia is expected. In addition, kidney function is known to impact elimination of the active M6G metabolite . However, neonates with HIE receiving hypothermia represent a distinct and vulnerable population from a pharmacologic perspective, and extrapolation of dose strategies from nonasphyxiated, normothermic neonates are likely inappropriate .…”
Section: Discussionmentioning
confidence: 99%
“…One-, two-, and three-compartmental models are observed, reflecting differences in sample times. Discrepancy can be observed in clearance values, whereas 10 studies reported morphine values, per kg or scaled (allometric, per 70 kg) [62,[76][77][78][79][80]83,84,86,90], © three studies reported morphine elimination clearances as elimination clearance of the metabolites (M3G and M6G) values [81,82,85].…”
Section: Glomerular Filtration Rate Correlated With Morphine Metabolitementioning
confidence: 99%
“…This will be preceded by background information concerning pain management in neonates ( © Section 1.1) (targeted indication for these drugs) as well as the patterns of enzyme maturation (Sections 1.2, 2, and 3). Those opioids were selected as both 90 have different metabolic pathways and are transformed by different iso-enzymes. Fentanyl undergoes phase I metabolism (Cytochrome P450 3A4, CYP3A4), whereas morphine undergoes phase II (UDP-glucuronosyltransferase-2B7, UGT2B7) metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Pediatric patients with renal dysfunction receiving morphine therapy are at increased risk of developing opioid toxicity due to accumulation of morphine metabolites. 42 Remifentanil is a very short-acting, pure mu receptor agonist that is equipotent to fentanyl. Its rapid onset and offset times make it particularly useful for procedural and short-term analgesia and anesthesia.…”
Section: Continuous Infusion Of Opioidsmentioning
confidence: 99%